Does International Financial Reporting Standards (IFRS) Impact Profitability Ratios of Listed Banks in Nigeria? - Erin, Olayinka; Oduwole, Foluke; Olojede, Paul; Arumona, Jonah (Journal of Accounting, Business and Finance Research, 2018)
This study provides an empirical analysis of the impact of IFRS on profitability ratios of eleven (11) banks in Nigeria. The study addresses the research hypotheses by comparing the key profitability ratios computed under the Pre-IFRS for three year period from 2009-2011 and three year period from 2013-2015 under the Post-IFRS regime. The study used Wilcoxon Signed Rank test and Normality test as a statistical method to analyze the data. The findings revealed that IFRS adoption has not produced any meaningful impact on the profitability ratios (PAT-EBIT, NPM, and OPM) at 5% level of significance. The finding implies that the adoption of IFRS does not have significant effects on profitability ratios of listed banks in Nigeria. The study recommends that investors and financial analyst should pay particular attention to all profitability ratios under this IFRS regime. Also, investors should not base their investment decisions on banks’ profitability in the short term but rather the long-term viability and performance should be taken into cognizance. This study provides original insight into the relevance of IFRS in determining the viability or otherwise of profitability ratios of listed banks in Nigeria.